Determination of hydrogen loading in the carrier system diphenylmethane/dicyclohexylmethane by depolarized Raman spectroscopy - Jander, Julius Hans; Kerscher, Manuel; Li, Shao; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
During the processes of hydrogenation or dehydrogenation of liquid organic hydrogen carriers (LOHCs), knowledge of the current degree of hydrogenation (DoH) is often essential. The present study shows that depolarized Raman spectroscopy allows the accurate determination of the DoH of the model LOHC system diphenylmethane (H0-DPM)/dicyclohexylmethane (H12-DPM) at temperatures up to 573 K. Using two independent experimental setups and binary mixtures of H0- and H12-DPM, a temperature-independent calibration factor could be obtained by analyzing Raman bands characteristic for the aromatic and aliphatic carbon rings. The successful transfer of the calibration to technical mixtures is validated by DoH measurements of samples from deliberately stopped hydrogenation reactions containing also the intermediate cyclohexylphenylmethane (H6-DPM) and of pure H6-DPM. Here, the average absolute deviation of the DoHs obtained by depolarized Raman spectroscopy from those measured analytically is 0.018, which demonstrates the applicability of the method at arbitrary and process-relevant temperatures.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Degree of hydrogenation; Depolarized Raman spectroscopy; Diphenylmethane; In-situ process monitoring; LOHC